STUDI TINGKAT KESESUAIAN PENGUPAHAN PADA BANK SYARIAH DI KOTA KENDARI (STUDI KASUS : BANK MUAMALAT KOTA KENDARI) - Wa Ode Sahrifan; Baheri Baheri; Teguh Permana (JEP (Jurnal Ekonomi Pembangunan), 2022)
The purpose of the study was to determine the level of suitability of wages at Bank Muamalat in Kendari City according to Islamic economic penalties. The research method used is descriptive research so that it is a description of the results of the distribution of the questionnaire (questionnaire). The data obtained were analyzed qualitatively and described in descriptive form.The results obtained that the wages of workers applied at Bank Muamalat use a time-based wage system, the amount of wages is determined based on time standards such as hourly, weekly or monthly (1). The level of suitability of wages applied to Bank Muamalat, Kendari City, based on this research, is mostly in accordance with the principles in the concept of Islamic Economics, namely the principles of fair, decent and reasonable. The wages given are in accordance with the terms and principles that have been determined in the view of Islamic economic law. so that the application is in accordance with the views of Islamic economic law (2).